Determining age-specific velocity thresholds for elite youth female soccer players. Issue 5 (1st December 2022) - Harkness-Armstrong, Alice; Till, Kevin; Datson, Naomi; Emmonds, Stacey
ABSTRACT: Purpose : This study aimed to establish age-specific velocity thresholds for Under (U)14 and U16 elite youth female soccer players. Methods : Data was collected using 10 Hz GPS units during 50 matches from 187 players (U14 n = 89; U16 n = 98). Spectral clustering identified velocity thresholds for high-speed running (HSR), very high-speed running (VHSR), and sprinting (SPR), for 699 half-match observations (U14 n = 369; U16 n = 330). Linear mixed modelling determined youth (U14 and U16) and age-group (U14 or U16) velocity thresholds, and compared distances covered between these and existing senior thresholds. The effect of playing position and playing half on velocity thresholds was also quantified. Results: Youth velocity thresholds of HSR (≥3.00 m·s −1 ), VHSR (≥4.83 m·s −1 ), and SPR (≥5.76 m·s −1 ) were estimated from the model. Age-group and playing position influenced velocity thresholds but playing half did not. Adoption of youth and age-group velocity thresholds resulted in greater distance covered at HSR, VHSR, and SPR (p < 0.001; moderate-large effect size [ES] = 0.86–1.97) compared to senior thresholds. Both age-groups covered similar distances (trivial-small ESs = 0.002–0.23) when adopting youth and age-group velocity thresholds. Conclusion: These youth thresholds provide an alternative to arbitrary velocity thresholds within the literature, and thresholds derived from senior players or other populations, to inform appropriate quantification and interpretation of physical data within this population.